Uji In Vitro Efek Ekstrak Etanol Biji Kakao (Theobroma cacao) sebagai Antibakteri terhadap Propionibacterium acnes (In Vitro Test of the Effect of Cocoa Beans (Theobroma cacao) Ethanolic Extract as an Antibacterial against Propionibacterium acnes) - Ariska Nur Aida; Enny Suswati; Misnawi Misnawi (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
Acne vulgaris is a chronic inflammatory disease of the pilosebaceous follicle, characterized by comedones, papules, pustules, cysts and nodules in certain sites of predilection, such as face, neck and back. Propionibacterium acnes are the most recognized bacteria as a key factor for the development of acne. The purpose of this research was to identify the antibacterial effect and Minimum Inhibitory Concentration (MIC) of ethanolic extract of Cocoa beans (T. cacao) against the growth of P. acnes by in vitro method. Antibacterial activity was measured by disk diffusion (Kirby Bauer) method. This was a quasi-experimental with posttest only control group design. Samples used was colony of P. acnes. Concentration of test solution used was 7.81; 15.62; 31.25; 62.50; 125; 250; 500; and 1000 mg/ml. Positive control used clindamycin suspension and negative control used sterile distilled water. By direct measurement, MIC was obtained at the dose of 31.25 mg/ml, by using linier regretion statistical analysis, the quantitatif MIC showed at the dose of 16.93 mg/ml. Analysis using ANOVA showed significance value p=0.000 (p<0.05). In conclusion, ethanolic extract of Cocoa beans had an antibacterial effect on P. acnes by in vitro method. Keywords: antibacterial effect, cocoa beans, Propionibacterium acnes